Challenges of Translating Cultural Terms in Jumla: A Nurse Story - Khadka, Dharmaraj (Janajyoti Journal, 2025)
This paper seeks to explore the challenges in translating culture-specific terms in Jumla: A Nurse Story, theEnglish rendition of Radha Poudel’s acclaimed Nepali narrative Khalanga Ma Hamala. The study criticallyexamines how the translator has dealt with culturally loaded words, ecological references, social customs,material objects, and administrative terminology in the context of Jumla, a remote district in Nepal. Drawingon key translation theories by Peter Newmark, Juliane House, and Clifford E. Landers, the paper analyzesvarious translation techniques such as adaptation, deletion, neutralization, interpolation, and functionalequivalence, and their effects on meaning, tone, and cultural authenticity. The translated text is examined forfidelity to the original’s emotional intensity, cultural embeddedness, and narrative flow. Particular attention isgiven to problematic translations, such as the misrepresentation or omission of Nepali ecological and religiousterms. They often dilute the source text’s richness. The paper concludes that while the translation successfullybridges linguistic gaps, it also compromises cultural integrity in certain areas which is relevant for translators,cultural theorists, and scholars working on Nepali literature in translation. It aims to contribute to the growingbody of research on literary translation and cross-cultural communication, especially from minoritizedlanguages to English.